Pengaruh Persaingan Akademik dan Digital terhadap Kesehatan Mental Mahasiswa Generasi Z : Analisis Studi Literatur - Nabila Aulia Syifa; Vira Febriana; Sri Mulyeni (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Mental health among Generation Z university students has become an increasingly important issue amid rising academic demands and the rapid development of digital life. Students today face various academic pressures, including competition for achievement, heavy coursework, and performance targets, which may negatively affect their psychological well-being. In addition, advances in digital technology have reshaped students’ daily lives, particularly through intensified information exposure and social comparison. This study aims to examine the influence of academic competition and digital dynamics on the mental health of Generation Z students using a literature review approach. The research employs a descriptive qualitative literature review method by analyzing 20 relevant scholarly articles published in national and international journals between 2018 and 2024. The findings indicate that academic competition is closely associated with increased levels of stress, anxiety, and emotional exhaustion among students. Prolonged academic pressure without adequate psychological support may lead to a decline in students’ psychological well-being. Furthermore, digital life reinforces psychological pressure through mechanisms of social comparison and self-presentation demands. However, several studies also identify protective factors, such as social support, mental health literacy, and emotional regulation skills, which help students manage academic and digital pressures more adaptively. Therefore, the mental health of Generation Z students is shaped by a complex interaction between academic competition and digital life, highlighting the need for comprehensive efforts from both individuals and educational institutions to promote students’ psychological well-being.